2020
DOI: 10.1016/j.landusepol.2019.104367
|View full text |Cite
|
Sign up to set email alerts
|

Institutional stakeholder participation in urban redevelopment in Tehran: An evaluation of decisions and actions

Abstract: Experimentation with citizen participation in urban redevelopments is increasing worldwide. This paper aims to scrutinise this trend through an in-depth case study of the decisions and actions taken by the institutional stakeholders involved in participatory urban redevelopment in Tehran, Iran. The discussion is based around two contrasting urban redevelopment areas which set out to adopt a participatory approach involving various stakeholders including institutions (the Municipality of Tehran and the Heritage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…One of the important outcomes of the workshops was the understanding that solutions to the problems should be realized by inter-agency coordination. This result is consistent with previous studies (Adu-Ampong, 2017;Akça, 2006;Bello et al, 2016;Durgun, 2007;Erfani & Roe, 2020;Eyassu et al, 2019;Hatipoglu et al, 2016;Kantawateera et al, 2013;Ladkin & Bertramini, 2020;Suherlan et al, 2018;Wan & Pinheiro, 2014;Yuksel et al, 1999;Zengingönül et al, 2012) which emphasize the lack of coordination and cooperation as among the important obstacles in sustainable tourism development and planning. For coordination issues, although a consensus was reached on the establishment of a platform in the workshops, the follow up session revealed that no action had been taken.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…One of the important outcomes of the workshops was the understanding that solutions to the problems should be realized by inter-agency coordination. This result is consistent with previous studies (Adu-Ampong, 2017;Akça, 2006;Bello et al, 2016;Durgun, 2007;Erfani & Roe, 2020;Eyassu et al, 2019;Hatipoglu et al, 2016;Kantawateera et al, 2013;Ladkin & Bertramini, 2020;Suherlan et al, 2018;Wan & Pinheiro, 2014;Yuksel et al, 1999;Zengingönül et al, 2012) which emphasize the lack of coordination and cooperation as among the important obstacles in sustainable tourism development and planning. For coordination issues, although a consensus was reached on the establishment of a platform in the workshops, the follow up session revealed that no action had been taken.…”
Section: Discussionsupporting
confidence: 92%
“…Byrd et al (2008) stated that stakeholders do not have a direct impact on tourism development; however, the level of understanding may contribute to social and cultural interactions between all stakeholders. Erfani and Roe (2020) emphasized that the quality of the whole process is liable to criticism when participation is considered inconsistent and perceived as unfair except for limited or intermittent resources. If the members of the community are ignored or treated unequally while accessing resources, they may feel rejected and, thus, both the process and the wider community cohesion may be damaged (Erfani & Roe, 2020).…”
Section: Stakeholders In the Development Of Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…An urban development project consists of several steps (e.g., preparation, planning, implementing) whereby specific results can be achieved through proposals, plans, changes, and recommendations [61]. Urban development includes issues such as transport, land use, infrastructure, housing, economic development, and especially sustainability, which require that a wide range of actors be included in the process [61,62]. The actors that influence or are influenced by urban planning are many and highly fragmented.…”
Section: Fourth Dimension: Involvingmentioning
confidence: 99%
“…Involving social actors enriches planning processes. Their participation can be described as the engagement and interaction among the actors, actions, and decisions [61]. Participation, indeed, is often associated with the concepts of democracy and justice: it is the element that makes it possible to achieve socio-cultural and economic objectives [61,67].…”
Section: Fourth Dimension: Involvingmentioning
confidence: 99%